DEVELOPMENT OF INTEGRATED SCIENCE MODULE BASED ON A CONTEXTUAL APPROACH TO SUBSTANCE PRESSURE MATERIALS AND ITS APPLICATIONS IN THE LIFE OF CLASS VIII SMP/MTs - Putri, Armelia; ., Yurnetti (Universe, 2024)
The research background was the unavailability of an included science module based on a contextual approach. This research purposes to make an integrated science module based on a contextual approach to substance pressure material and its application in the life of class VIII SMP/MTs that have criteria in valid and practical. This research type was research and development (R&D). Product developed used model of uses 4-D which is modified into 3-D. The process taken were define, design, and develop. In the process of validation, the module was validated by 3 lecturers as validator, namely material expert validator, linguist, and design expert. The results of the integrated science module development are valid from the validation sheets results that have been assessed by each validator with an overall average of 87.41% with criteria in very valid. In the process of practical, the module was tested by 3 teachers and 26 students of class VIII MTsN 6 Tanah Datar. Practicality results were obtained from practicality sheets (teacher and student response questionnaires) which got 86.90% practicality scores by teachers with very criteria in practical and 82.13% practicality by students with criteria in very practical. The conclusion of this research was to make an included science module based on a contextual approach to substance pressure and its application in the life of class VIII SMP/MTs which was valid and practical to be used in the integrated process of science learning.